The dynamics of blood indexes in rats after ceramic biomaterial implantation in defects of the femur methaphis and diaphysis - Shimon, Vasyl; Meklesh, Yurii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: on the base of blood markers dynamics we determined the influence of ceramic material on the rats’ organism and bone regeneration after implantation in the femur methaphis and diaphysis. Methods: study was made on rats male, age of 4.5 months in 4 groups with 9 rats in each group. The 1st group — the methaphis femur defect was empty, in the 2nd group — the defect was filled with ceramic material. The 3rd and 4th g roups – diaphysis d efects were made correspondently. For implantation we used ceramic material consisted of 57.77 % of hydroxyapatite and 47.23 % of threecalciumphosphate beta. In 7, 14, 28, 56 days clinical and biochemistry analyses were made. Results: biochemistry indexes of the liver functional state, glucose, urea did not change after implantation of ceramic material. In 7 days after making of defect in the femur we have found moderate leukocytosis. After ceramic material implantation in rats indexes of hematology analysis did not change. We have found decreasing of creatinine level in 7 days in all groups: in the 1st — 28.2 % , in the 2nd — 29.2 %, in the 3rd — 21.6 %, in the 4th — 21.9 %. Glycoproteins, chondroitin sulfates, alkaline phosphatase activity in blood plasma have shown the revitalization of regeneration process on early stages and these indexes were decreased in late follow-up, it was more pronounced after ceramic material implantation. In 56 days the blood indexes did not differ from the data obtained from intact rats. Conclusions: it was found that after implantation of ceramic material there was not toxic effect on rats’ organism. Indexes of glycoproteins, chondroitin sulfates, alkaline phosphatase activity found in blood testified of more pronounced regeneration in the place of bone defect with ceramic material implantation.